Os impactos nos indicadores econômico-financeiros da Petrobras causados pela corrupção desvendada na operação lava jato: um estudo de caso - Pinho, Paulo Victor de (2017)
This study aimed to analyze what was the impact of Lava Jato Operation in the financial ratios of Petrobras. The importance of this company for the economic development of Brazil and thte effects of fraud on its results are the reasons for carrying out this research. By means of a case study through with quantitative and qualitative approach, using documental research procedures, the main financial ratios were calculated in the period of 2012 to 2016. The results pointed to a substantial worsening in those ratios were intrinsically linked to the fraud. One factor highlighted as a reason for, is related to the accounting recognition of impairment losses. According to the entity´s management, world decreasing in prices of petroleum was one of the causes of reduction results, but this could not have identified through this research.